Evaluation of STK17B as a cancer immunotherapy target utilizing highly potent and selective small molecule inhibitors - Scheuplein, Felix; Renner, Florian; Campbell, John E.; Campbell, Robert; De Savi, Chris; Eckmann, Jan; Fischer, Holger; Ge, Jie; Green, Luke; Jakob, Peter; Kim, Joseph L.; Kinkema, Caitlin; et al. (Frontiers in Immunology, 2024)
Introduction The serine/threonine kinase 17B (STK17B) is involved in setting the threshold for T cell activation and its absence sensitizes T cells to suboptimal stimuli. Consequently, STK17B represents an attractive potential target for cancer immunotherapy. Methods To assess the potential of STK17B as an immuno-oncology target, we developed potent and selective tool compounds from starting points in Blueprint Medicines Corporation's proprietary kinase inhibitor library. To characterize these molecules, enzyme and cellular assays for STK17A and STK17B were established to drive chemistry optimization. Mass spectrometry-based phosphoproteomics profiling with tool inhibitors led to the identification of Ser19 on myosin light chain 2 as STK17B substrate, which is then developed into a flow cytometry-based pharmacodynamic readout of STK17B inhibition both in vitro and in vivo. Results In a mouse T cell activation assay, STK17B inhibitors demonstrated the ability to enhance interleukin-2 (IL-2) production. Similarly, treatment with STK17B inhibitors resulted in stronger cytokine secretion in human T cells activated using a T cell bispecific antibody. Subsequent chemistry optimization led to the identification of a highly selective and orally bioavailable tool compound, BLU7482. In vivo, STK17B inhibition led to dose-dependent modulation of myosin light chain 2 phosphorylation and enhanced priming of naïve T cells, as determined by upregulation of CD69, IL-2 and interferon-γ secretion. In line with increased T cell activation, treatment with STK17B inhibitor enhanced antitumor activity of anti–PD-L1 antibody in the MCA205 model. Conclusions In summary, we successfully identified and optimized STK17B kinase inhibitors which led to increased T cell responses in vitro and in vivo. This allowed us to evaluate the potential of STK17B inhibition as an approach for cancer immunotherapy.